Exposure to phthalate‐containing prescription drugs and the risk of colorectal adenocarcinoma: A Danish nationwide case‐control study. Issue 4 (22nd February 2019) - Ennis, Zandra Nymand; Pottegård, Anton; Ahern, Thomas Patrick; Hallas, Jesper; Damkier, Per
Abstract: Purpose: Some drug products contain phthalates as excipients, and in vitro studies have demonstrated that phthalates interfere with cellular mechanisms involved in colorectal cancer development. We therefore examined the association between cumulative phthalate exposure from drug products and risk of colorectal adenocarcinomas. Methods: We used the Danish Cancer Registry to identify all patients with incident colorectal adenocarcinoma from 2008 to 2015 (n = 25 814). Each cancer case was matched to ten population controls. Linking information from Danish registers, we quantified cumulative phthalate exposure to the ortho‐phthalates diethyl phthalate (DEP) and dibutyl phthalate (DBP) as well as enteric phthalate polymers from orally administered drugs. The association between cumulative phthalate exposure and colorectal cancer was estimated using conditional logistic regression. Results: Cumulative exposure to ortho‐phthalates exceeding 500 mg was associated with lower odds of colorectal cancer diagnosis (ORadj  = 0.89; 95% CI, 0.81‐0.96). Similar associations were observed for all DEP exposure exceeding 500 mg. Subgroup analysis excluding NSAID users, demonstrated that ortho‐phthalate exposure was positively associated with colorectal cancer (ORadj  = 1.26; 95% CI, 1.05‐1.51). Conclusion: We found an apparent overall protective effect of cumulative phthalate exposure from drug excipients for colorectal adenocarcinoma. Omitting NSAID users reversed the signal and suggested a slightly increased risk associated with high cumulative ortho‐phthalate exposure.